Sistema web para la gestión de rol de pagos en la fábrica de lácteos El Ranchito - Tipán Rojas, Norma Soledad (2017)
The present project consisted of the development of a Web System with a query module in Android, with the purpose of automating the Assistance registration and the Management of the Payment roll into the "El Ranchito Dairy Factory" in the Cotopaxi Province, Salcedo Canton, for performing the above mentioned has been determined the use of development platforms Play Framework and Android Studio. The first is the main tool in development because it is based on the Java language and is oriented to the development of web applications using a software architecture known as Model Vista Controller. The second is based on the integrated development environment (IDE) for the development of applications with Android operating system. Besides, Android Studio offers functions that increase productivity during the Apps compilation for Android. The use of the PostgreSQL database engine as a storage medium was also considered. This project was developed based on a field research which allowed to know the problem and the requirements necessary for the development of the Web System with the consultation module on Android using the biometric technology that is based on the verification of the fingerprints, that are unique and unrepeatable for each person and subsequently, they would be consulted in the database. The main objective of the project was to develop a Web Application and mobile using development methodologies, in this case used the agile methodology "SCRUM", which allows an adequate organization throughout the development cycle and for the work of the query module in Android was specifically using the "Mobile-D" methodology which allows to achieve very fast progress cycles in small equipment of effectively and efficiently.